ANALISIS SEKTOR POTENSIAL KABUPATEN TANJUNG JABUNG TIMUR - Wiyan Mailindra; Muhammad Amali (Universitas Batanghari Jambi, 2017)
The purpose of this study was to look economic sectors that became the base sector and to look friction economic sectors in Tanjung Jabung Timur District. The method used Location Quotient analysis and shift share analysis. The data used Gross Regional Domestic Product. The results showed that base sector was mining and digging sectors, while for friction, mining sector has the highest Pnij value, then the highest Ppij or industry mix was trading, hotel and restaurant. Then, PPWij or competitive superiority was agriculture sector. The next, the highest Dij or change or enhancement during analisys period was agriculture sector. The policy implication of this research was develop the economic sector based on job creation. Hopefully, it will be able to absorb the workforce and increase the income of the society, whose the end purpose was the achievement of the society welfare.Keywords: Base sector, competitive superiority, friction sector, Society welfare